SOIL ANALYSIS ON MICROBIOLOGICAL INDICATOR VALUES IN THE AREA OF UNDERGROUND NATURE GAS STORAGE - E. V. Pleshakova; C. T. Ngun; M. V. Reshetnikov (Юг России: экология, развитие)
The aim is to conduct the biodiagnosis of soil sampled in the area of the underground storage of natural gas (UGS) (Stepnoye village, Saratov region) with the use of microbiological analysis.Methods. In the course of the work, using Koch’s solid medium method were estimated the following: the total number of heterotrophic microorganisms on meat peptone agar, amount of methylotrophic, hydrocarbon oxidizing, ironoxidizing and sulfur-oxidizing bacteria in the respective selective mediums; as well as the hydrogen index, oxidation-reduction potential and magnetic susceptibility of the soil.Results. Microbiological analysis of the soil in the Stepnovsky UGS area has shown changes in soil biocenoses. A reduced content of heterotrophic microorganisms was detected in comparison with background samples. In a number of samples, we also discovered an increased content of hydrocarbon-oxidizing and methylotrophic microorganisms, including obligate ones, which suggest the methane entering the upper layers of the soil. An increased content of sulfur-oxidizing bacteria was also detected; the presence of iron-oxidizing microorganisms in the soil was shown.Conclusions. The revealed features in the content of indicator microorganisms in the soil sampled in the area of the underground storage of natural gas, indicating the development of specialized soil microorganisms, confirmed the presence of contaminants in the soil which are hydrocarbons and sulfur compounds. The use of microbiological indicator values seems promising for environmental monitoring of soils in the areas of gas storage and early detection of methane leakage.